Mechanisms, pathophysiological roles and methods for analyzing mitophagy – recent insights - Williams, Jessica A.; Ding, Wen-Xing (Biological chemistry, 2018)
In 2012, we briefly summarized the mechanisms, pathophysiological roles and methods for analyzing mitophagy. As then, the mitophagy field has continued to grow rapidly, and many new molecular mechanisms regulating mitophagy and molecular tools for monitoring mitophagy have been discovered and developed. Therefore, the purpose of this review is to update information regarding these advances in mitophagy while focusing on basic molecular mechanisms of mitophagy in different organisms and its pathophysiological roles. We also discuss the advantage and limitations of current methods to monitor and quantify mitophagy in cultured cells and mouse tissues.